EARLY BIRD SEBAGAI MEDIA PEMBELAJARAN BAHASA INGGRIS DI SD - A. B. PRABOWO K. A.; Faiza Hawa; Fitri Yulianti (Universitas PGRI Semarang, 2010)
Abstract: Early Bird is a current product applied in Elementary School as a media of English teaching. It implies the progress of teaching learning process which enhances students?óÔé¼Ôäó ability in understanding English vocabularies and teacher?óÔé¼Ôäós creativity. This media has been acknowledged to Elementary English teachers who join in Gubug English Teachers?óÔé¼Ôäó Association, Grobogan. This media can help the English teachers create an alternative media based on the mechanism of Early Bird. It means that Early Bird cannot only be used as a media, but also can inspire the teachers to create an alternative media in teaching English in the Elementary school.Key words: Early Bird, alternative media, English teaching